"Imagine the streets": The spatial dimension of protests' transformative effects and its role in building movement identity. (January 2017) - Daphi, Priska
Abstract: The recent wave of occupations highlighted how closely space and social movements are related. While this revived scholarly interest in the role of space during protests, little attention so far has been paid to the role of space in protests' long-term internal effects. Bringing together the literatures on transformative effects and space in social movements, the paper examines the role of protests' spatiality in their transformative effects, drawing on a narrow approach to space. The analysis focuses in particular on effects on collective identity building in social movements. Based on interviews and focus groups with activists in 2011, the paper examines the long-term effects of an incisive protest event of the Global Justice Movement (GJM) in Europe, the protests against the G8 summit in Genoa in 2001. The paper shows that this event's spatiality plays a crucial role in building movement identity several years later: it provides activists with interpretational devices to delineate the GJM's internal and external boundaries. The paper thus underlines that research on transformative effects can considerably profit from considering spatiality.